Usewear analysis of mesolithic and neolithic stone tools from Mala Triglavca, Trhlovca and Pupičina peć - Petru, Simona (Documenta Praehistorica, 2004)
In this paper the results of the usewear analysis of Mesolithic and Neolithic stone tools from three cave sites - Mala Triglavca and Trhlovca in the Slovenian Karst and Pupičina peć in Croatian Istra will be presented. Stone tools were examined under the light microscope at 50 - 200 x magnifications, and some additional physical and chemical analyses were undertaken. Various uses of the tools were determined and conclusions regarding the economies at those sites were drawn.
Keywords: arheološke najdbe; prazgodovina; mezolitik; neolitik; kraške jame; List of caves in Slovenia; kameno orodje; karst; Kras; Slovenia; Slovenija; Istra; Istria; Croatia; Hrvaška